Making the white man's West: whiteness and the creation of the American West - Pierce, Jason E., author; University Press of Colorado, publisher (Colorado State University. Libraries, 2016)
The West, especially the Intermountain states, ranks among the whitest places in America, but this fact obscures the more complicated history of racial diversity in the region. In Making the White Man's West, author Jason E. Pierce argues that since the time of the Louisiana Purchase, the American West has been a racially contested space. Using a nuanced theory of historical 'whiteness,' he examines why and how Anglo-Americans dominated the region for a 120-year period. In the early nineteenth century, critics like Zebulon Pike and Washington Irving viewed the West as a 'dumping ground' for free Blacks and Native Americans, a place where they could be segregated from the white communities east of the Mississippi River. But as immigrant populations and industrialization took hold in the East, white Americans began to view the West as a 'refuge for real whites.' The West had the most diverse population in the nation with substantial numbers of American Indians, Hispanics, and Asians, but Anglo-Americans could control these mostly disenfranchised peoples and enjoy the privileges of power while celebrating their presence as providing a unique regional character. From this came the belief in a White Man's West, a place ideally suited for 'real' Americans in the face of changing world. The first comprehensive study to examine the construction of white racial identity in the West, Making the White Man's West shows how these two visions of the West--as a racially diverse holding cell and a white refuge--shaped the history of the region and influenced a variety of contemporary social issues in the West today.--Provided by publisher.
Introduction: Whiteness and the Making of the American West -- Part I. From Dumping Ground to Refuge: Imagining the White Man's West, 1803-1924 -- "For Its Incorporation into Our Union": The Louisiana Territory and the Conundrum of Western Expansion -- A Climate of Failure or One "Unrivaled, Perhaps, in the World?" -- "The Ablest and Most Valuable Fly Rapidly Westward": Climate, Racial Vigor and the Advancement of the West, 1860-1900 -- Indians not Immigrants: Charles Fletcher Lummis, Frank Bird Linderman and the Complexities of Race and Ethnicity in America -- Part II. Creating and Defending the White Man's West -- The Politics of Whiteness and Western Expansion -- "Our Climate and Soil is Completely Adapted to their Customs": Whiteness, Railroad Promotion and the Settlement of the Great Plains -- Unwelcome Saints: Whiteness, Mormons, and the Limits of Success -- Violence in Defense of the White Man's West -- Conclusion: The Limits and Limitations of Whiteness.
Keywords: West (U.S.) -- Race relations -- History; Whites -- West (U.S.) -- History; Whites -- Race identity -- West (U.S.) -- History; British Americans -- West (U.S.) -- History; Racism -- West (U.S.) -- History; Cultural pluralism -- West (U.S.) -- History; Frontier and pioneer life -- West (U.S.); West (U.S.) -- History -- 19th century; West (U.S.) -- History -- 20th century